Achievements of the Hungarian Presidency of the Council in Promoting the Schengen Area as a Strategic Asset for the EU - Töttős, Ágnes (Pécs journal of international and European law, 2026)
Schengen not only remains a project designed for the benefit of the people but it has also evolved into a strategic asset of the Union, in three ways. First, as an essential enabler of the Single Market, second, as one of the EU’s strongest response to the challenges of a world, and third, as a force for unity. In its Presidency Programme for the second half of 2024, Hungary aimed at facilitating strong European borders and a crisis-resilient system. The aim of this study is to examine to what extent the Hungarian Presidency was able to promote the Schengen area as a strategic asset for the EU, and will also highlight how the Hungarian Presidency helped achieving European goals in strengthening the Schengen area, especially as regards the digitalisation of procedures and the interoperability architecture, the strengthening of Schengen governance, and facilitating the full accession of Romania and Bulgaria to the Schengen area.